Environmental pollution ecology and human health - Reddy, Gottipolu R.; Flora, S. J. S.; Basha, Riyaz (Narosa, 2012)
ENVIRONMENTAL POLLUTION: Ecology and Human Health provides an interdisciplinary approach to the subject of Environment and health integrating biochemical, physiological, pharmacological, toxicological, behavioral and ecological responses to different types of environmental challenges. The information presented provides modern molecular insights into mechanistic basis of environmental health effects of various environmental toxicants including prevention and therapeutics.